The Sociology of Bourdieu: evaluation of the scientific production of productivity researchers in Information Science - Alves, Bruno Henrique; Tannuri de Oliveira, Ely Francina [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
The scientific field of Information Science is a hierarchical space of positions and is formed by objective relations. This study aims to understand the generation and construction of knowledge by researchers in Information Science with productivity grants in Brazil. Specifically, this study sets out to present Brazilian researchers in Information Science with research productivity grants and to group the different articles they have written, according to the themes of the Working Groups in the Brazilian National Association for Research and Post-Graduate Education in Information Science, known as ANCIB. The research sample consisted of a total of 47 researchers in Information Science with productivity grants, in the first five years from 2005 to 2009, and of 56 researchers in the second five-year period from 2010 to 2014. A total of 317 articles were published in journals in the first five years, and 597 in the second five-year period. These articles were used to make groupings based on the themes of the 11 Working Groups of the Brazilian National Association for Research and Post-Graduate Education in Information Science and to generate the two-mode networks by use of the Ucinet software. We have found that scientific work aims to establish adequate knowledge to operate its development from the objective relations presented by the researchers. We conclude that Brazilian researchers in Information Science with productivity grants involved in such a power game have specific interests defined by that game's mode of operation; that is, there is always competition for prizes, for the best papers, for scientific coordination, among other kinds of competition.
Keywords: Scientific field; Knowledge Construction; Working Groups of the ANCIB